A compact circularly polarized dielectric resonator antenna with MIMO characterizations for UWB applications - Shahid Khan; Owais Khan; Syed Ahson Ali Shah; Bilal Tariq Malik; Neelam Gohar; Slawomir Koziel (Scientific Reports, 2024)
Abstract Ultra-wideband (UWB) technology is extensively used in indoor navigation, medical applications, and Internet of Things devices due to its low power consumption and resilience against multipath fading and losses. This paper examines a multiple-input multiple-output (MIMO), circularly polarized (CP) dielectric resonator antenna for UWB systems. Compact form factor, high gain, wideband response, improved port isolation, and high data rates are the major design goals. This arrangement consists of two identical DRAs with self-decoupled orthogonal orientations eliminating the need for extra decoupling structures while achieving an impressive maximum isolation of 43 dB. The corner-edge feeding mechanism of the extended feedline generates two orthogonal E-fields, facilitating circular polarization. Additionally, a printed hook-shaped stub integrated with the ground plane enhances CP performance across the two operating bands without altering the DR structure. Fabrication and testing exhibit an impressive 133 $$%$$ % impedance bandwidth (2.5–14 GHz) with high port isolation. For a 3 dB axial ratio reference, the single-element design exhibits axial ratio bandwidths (ARBW) of 1.2 GHz (3.6–4.8 GHz) and 0.8 GHz (9.3–10.1 GHz). Remarkably, the MIMO configuration achieves a single ARBW of 0.5 GHz (3.9–4.4 GHz). Detailed investigations of MIMO performance parameters, including diversity gain, envelope correlation coefficient, channel capacity loss, and total active reflection coefficient, underscore the design’s efficacy, making it a good choice for UWB wireless applications.